3D‐Bioprinted Osteoblast‐Laden Nanocomposite Hydrogel Constructs with Induced Microenvironments Promote Cell Viability, Differentiation, and Osteogenesis both In Vitro and In Vivo. Issue 3 (24th November 2017) - Zhai, Xinyun; Ruan, Changshun; Ma, Yufei; Cheng, Delin; Wu, Mingming; Liu, Wenguang; Zhao, Xiaoli; Pan, Haobo; Lu, William Weijia
Abstract: An osteoblast‐laden nanocomposite hydrogel construct, based on polyethylene glycol diacrylate (PEGDA)/laponite XLG nanoclay ([Mg5.34 Li0.66 Si8 O20 (OH)4 ]Na0.66, clay )/hyaluronic acid sodium salt (HA) bio‐inks, is developed by a two‐channel 3D bioprinting method. The novel biodegradable bio‐ink A, comprised of a poly(ethylene glycol) (PEG)–clay nanocomposite crosslinked hydrogel, is used to facilitate 3D‐bioprinting and enables the efficient delivery of oxygen and nutrients to growing cells. HA with encapsulated primary rat osteoblasts (ROBs) is applied as bio‐ink B with a view to improving cell viability, distribution uniformity, and deposition efficiency. The cell‐laden PEG–clay constructs not only encapsulated osteoblasts with more than 95% viability in the short term but also exhibited excellent osteogenic ability in the long term, due to the release of bioactive ions (magnesium ions, Mg 2+ and silicon ions, Si 4+ ), which induces the suitable microenvironment to promote the differentiation of the loaded exogenous ROBs, both in vitro and in vivo. This 3D‐bioprinting method holds much promise for bone tissue regeneration in terms of cell engraftment, survival, and ultimately long‐term function. Abstract : An osteoblast‐laden nanocomposite hydrogel construct is developed using a two‐channel 3D‐bioprinting method for bone regeneration. The cell‐laden scaffold reveals high cell viability (>95%) in the short term after 3D‐bioprinting and exhibits excellent osteogenic capability both in vitro and in vivo in the long term due to the bioactive ions that are gradually released.